Genome-wide association study of seedling–plant resistance to stripe rust in bread wheat (Triticum aestivum L.) genotypes - Atsbeha, Genet; Mekonnen, Tilahun; Brhane, Haftom; Kebede, Mulugeta; Haileselassie, Teklehaimanot; Tesfaye, Kassahun (Frontiers in Plant Science, 2025)
Fungal diseases, such as stripe rust, are major bottlenecks in Ethiopian wheat production. They can significantly reduce yields and impact regional food security. To enhance Ethiopian wheat production, incorporating genetically resistant cultivars into breeding programs is essential. Accordingly, this study aimed at exploring the genome-wide association of seedling resistance in 178 wheat genotypes to identify genetic markers linked to yellow rust resistance. The panel was phenotyped for yellow rust seedling resistance at Kulumsa Agricultural Research Centre Pathology Laboratory. Additionally, the association panel was genotyped using the genotyping-by-sequencing (GBS) platform and a total of 6,788 polymorphic SNPs were used in genome-wide association analysis to identify effective yellow rust resistance genes. The Genome Association and Prediction Integrated Tool (GAPIT) was used to analyze marker–trait associations. The overall linkage disequilibrium (LD) decreased within an average physical distance of 31.44 Mbp at r2 = 0.2. Marker-trait association (MTA) analysis revealed 102 loci that are significantly (p = 0.001) related to yellow rust seedling–plant resistance. The majority of the discovered resistance quantitative trait loci (QTLs) were located on the same chromosomes as previously reported QTLs for yellow rust resistance, specifically on chromosomes 1A, 1B, 2A, 2B, 2D, 3A, 3B, 3D, 5A, 5B, 5D, 6A, 6B, 6D, 7A, 7B, and 7D. However, seven of the detected MTAs had not previously been documented in wheat literature or the International Wheat Genome Sequencing Consortium (IWGSC), suggesting that they may represent potentially novel loci for stripe rust resistance. Zooming in on QTL regions in the IWGSC RefSeq Annotation v1.1 revealed critical disease resistance-associated genes involved in plant defensive mechanisms against pathogen infections. The newly identified QTLs will be useful for marker-assisted wheat breeding to boost resistance to stripe rust.